A Two-Parameter Continuation Method for Rotating Two-Component Bose-Einstein Condensates in Optical Lattices (Communications in Computational Physics, 2018)
We study efficient spectral-collocation and continuation methods (SCCM)for rotating two-component Bose-Einstein condensates (BECs) and rotating two-component BECs in optical lattices, where the second kind Chebyshev polynomials are usedas the basis functions for the trial function space. A novel two-parameter continuationalgorithm is proposed for computing the ground state and first excited state solutionsof the governing Gross-Pitaevskii equations (GPEs), where the classical tangent vector is split into two constraint conditions for the bordered linear systems. Numericalresults on rotating two-component BECs and rotating two-component BECs in optical lattices are reported. The results on the former are consistent with the publishednumerical results.